Dve teoriji kapitalističnega gospostva - Bembič, Branko (Teorija in praksa, 2011)
This article first discusses the Lacanian critique of capitalism and its overlooked relation to Keynesian theory or, rather, to the Keynesian political project. Basing itself on Kaleckian theory, it then proceeds with an historical analysis of the Keynesian project. Through an analysis of the most relevant aspects of the economic history of capitalist economies in the second half of the twentieth century, this article demonstrates the deficiencies in the basic thesis of the Lacanian critique of capitalism and examines the consequences for political theory that follow from this critique's rootedness in the historical horizon of the Keynesian project.
Keywords: Kapitalizem; Postkeynesianizem; Teoretska psihoanaliza; Postkeynesianism; Capitalism; lacanovska teorija; Theoretical psychoanalysis